Building the successful online course - Haley, Kenneth L.; Heise, Karen (Emerald Publishing Limited : IAP-Information Age Publishing Inc., 2008)
This book will be a practical guide to developing and implementing online courses. It is based on a model now in use at Paris Junior College in Paris, TX which has often resulted in retention rates of over 90%. It will be a comprehensive practitioner's guide including information on retention and multimedia support.This book will be a guide to anyone who may wish to teach online in any subject area at any level. The book provides actual examples of problems and solutions concerning online courses and also includes examples of supporting documents. Through a supporting Web site, the book will include actual examples of multimedia support now in use The book might also be used in graduate classes as a curriculum development guide. Readers would use the book as a guide as they actually create online courses. This would take most of the guess work out of course creation and provide a solid foundation for distance learning programs. The book provides a simple yet effective approach to online learning. It uses a model that has been proven to be effective with retention rates to support the contention. It provides information on a retention study and multimedia support as well, two areas that have not been addressed very often to this point.